The middleman [compact disc, unabridged] - Steinhauer, Olen (Macmillan Audio, 2018)
Told from the individual perspectives of an FBI agent, an undercover agent within the group, a convert to the terrorist organization, and a writer on the edges of the whole affair, this is another tightly wound thriller, and an intimate exploration of the people behind the politics, from a master of suspense.